Pengaruh Residu Berbagai Dosis Bokashi Dan Pupuk Sp-36 Terhadap Pertu Mbuhan Dan Hasil Tanaman Kacang Hijau (Vigna radiata L.) - Maya Fadilah; Krisnarini Krisnarini; Priyadi Priyadi; Yatmin Yatmin (JURNAL WACANA PERTANIAN, 2023)
Organic fertilization of cow manure bokashi and inorganic fertilizer SP-36 is an alternative to improve soil fertility in red-yellow podzolic soil. However, due to its slow availability, the application of this fertilizer from previous plantings still leaves residue to improve the quality of mung beans in subsequent plantings. The aims of the study were to determine: 1) The effect of various residual doses of bokashi fertilizer on the growth and yield of mung bean. 2) The effect of various residual doses of SP-36 fertilizer on the growth and yield of mung bean. 3) Interaction of various doses of bokashi and SP-36 fertilizer residues on the growth and yield of mung bean. The research was carried out in the experimental garden of the Dharma Wacana College of Agricultural Sciences, Margorejo Subdistrict, Metro City, from February to April 2021. The study used a Complete Randomized Block Design which was arranged in a factorial manner with three replications. The first factor was residues of cow manure Bokashi fertilizer (B) which consisted of three levels, namely dose of 5 tons/ha (b1), 10 tons/ha (b2), and 15 tons/ha (b3). The second factor was SP-36 (P) fertilizer residue which also consisted of three levels, namely dose of 150 kg/ha (p1), 200 kg/ha (p2), and 250 kg/ha (p3). The results showed that residues of various doses of bokashi and SP-36 had no significant effect. No interaction was found between residues of bokashi fertilizer and SP-36 on the growth and yield of mung bean. However, mung beans show a fairly good production.